2015
DOI: 10.4236/ojer.2015.41004
|View full text |Cite
|
Sign up to set email alerts
|

Coulomb Stress Perturbations Related to the Al Hoceima (Morocco) Earthquakes of 1994 and 2004

Abstract: This paper exposes the results of the study of the stress perturbations caused by the Al Hoceima (Morocco) earthquakes of 1994 and 2004 by means of Coulomb modeling. Modeling was based on the compilation of all the studies carried out after both events, including seismological (location and depth of the main shocks and aftershocks), seismotectonic (source parameters, stress field), geodetic (GPS), tomographic and geological ones. It shows that the first earthquake is likely to have induced the second one when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…For instance, the CSC during the seismic crisis of 2016 ( Figure 7) shows that there is an increase in CS to the north and to the south, spanning the Al-Idrissi FZ and the Algarrobo-Herradura-Djibouti banks off the Spanish margin ( Figure 1). An interesting feature is that the area NE of Al Hoceima, which was in a CS decrease zone [3], has undergone an increase of CS after 2016, and should be considered in the next years. The same can be said about the Alboran ridge, which has been activated in 2016.…”
Section: What About the Next Large Earthquake (And Tsunami)?mentioning
confidence: 99%
See 3 more Smart Citations
“…For instance, the CSC during the seismic crisis of 2016 ( Figure 7) shows that there is an increase in CS to the north and to the south, spanning the Al-Idrissi FZ and the Algarrobo-Herradura-Djibouti banks off the Spanish margin ( Figure 1). An interesting feature is that the area NE of Al Hoceima, which was in a CS decrease zone [3], has undergone an increase of CS after 2016, and should be considered in the next years. The same can be said about the Alboran ridge, which has been activated in 2016.…”
Section: What About the Next Large Earthquake (And Tsunami)?mentioning
confidence: 99%
“…CSC calculations were carried out taking into account the regional state of stress, derived from our previous R4DT determination for the Al Hoceima area [26]: σ 1 and σ 3 horizontal at 150˚E and N60˚E respectively. The stress magnitudes used by software Coulomb are 100 bar for σ 1 ; 30 bar for σ 2 ; and 0 bar for σ 3 . No vertical gradient was taken into account.…”
Section: Input Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…(2) The recurrence of earthquakes based only on time has been seriously questioned by the seismotectonic studies, which have shown that, after an earthquake, stress can be transferred to other segments or to the tips of the fault (Cowie and Scholz 1992;King et al 1994). Moroccan examples are those of the Mw~5 Erfoud earthquakes of 23 and 30 October 1992 (Bensaid et al 2012), and the Mw~6 Al Hoceima area earthquakes of 1994, 2004 and 2016 (Medina 2015;Medina and Cherkaoui 2017).…”
Section: Slip and Uplift Ratesmentioning
confidence: 99%